Performance management implementation challenges in South African local government: Evidence from KwaDukuza Local Municipality - Nyika, Farai; Mohangi, Prashina (JPAS (Journal of Public Administration Studies), 2024)
South African municipalities are mandated to provide accountable governance, ensure sustainable service delivery, promote economic and social development, provide a healthy and safe environment, and include communities in the affairs of local government, as contained in the country’s constitution. However, many municipalities are struggling to provide these services to their residents. Performance management is the tool that can contribute to solving service delivery challenges as the performance management contracts of all municipal employees are meant to be aligned to their Integrated Development Plans. This study investigates how performance management implementation challenges are negatively affecting the ability of KwaDukuza Local Municipality to deliver on their core mandate. The study uses a qualitative methodology with 14 semi-interviews of municipal managers and councillors. It finds that weak institutional capacity, low levels of accountability, poor implementation and poor communication of performance management practices are hindering the KwaDukuza Municipality. The authors recommend that the provincial government increases its support to the local municipality, increased managerial accountability and for managers to be capacitated to implement the performance management systems.